2017
DOI: 10.1038/ncomms14859
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological inhibition of adipose triglyceride lipase corrects high-fat diet-induced insulin resistance and hepatosteatosis in mice

Abstract: Elevated circulating fatty acids (FAs) contribute to the development of obesity-associated metabolic complications such as insulin resistance (IR) and non-alcoholic fatty liver disease (NAFLD). Hence, reducing adipose tissue lipolysis to diminish the mobilization of FAs and lower their respective plasma concentrations represents a potential treatment strategy to counteract obesity-associated disorders. Here we show that specific inhibition of adipose triglyceride lipase (Atgl) with the chemical inhibitor, Atgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
172
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(190 citation statements)
references
References 38 publications
8
172
0
Order By: Relevance
“…To avoid the accumulation and toxic effects of FFAs, one could target several pathways of the fatty acid metabolism: lipolysis, b-oxidation, or lipogenesis. Pharmacological inhibition of one of the major lipases, adipose triglyceride lipase (ATGL), was successful in correcting high-fat diet-induced insulin resistance and hepatosteatosis in mice (Schweiger et al, 2017). Several potent inhibitors that are directed toward the other major lipase, HSL, have recently been produced and might provide an attractive alternative to treat sepsis (Ogiyama et al, 2017).…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…To avoid the accumulation and toxic effects of FFAs, one could target several pathways of the fatty acid metabolism: lipolysis, b-oxidation, or lipogenesis. Pharmacological inhibition of one of the major lipases, adipose triglyceride lipase (ATGL), was successful in correcting high-fat diet-induced insulin resistance and hepatosteatosis in mice (Schweiger et al, 2017). Several potent inhibitors that are directed toward the other major lipase, HSL, have recently been produced and might provide an attractive alternative to treat sepsis (Ogiyama et al, 2017).…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…The fact that plasma FFAs are linked to insulin resistance (Schweiger et al, 2017) and neuroinflammation (Butler et al, 2017) renders lipolysis an attractive target to improve insulin sensitivity. HSL and MGL are crucial lipases involved in lipolysis and degradation of stored triglycerides into FFA and glycerol (Bolsoni-Lopes & Alonso-Vale, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of circulating FFA play crucial role in insulin resistance and, hence, in the pathogenesis of type II diabetes mellitus (Arner, 2003;Karpe, Dickmann, & Frayn, 2011;Morigny, Houssier, Mouisel, & Langin, 2016;Schweiger et al, 2017). Moreover, MGL is involved in neuroinflammation by releasing proinflammatory eicosanoids and cytokines (Butler et al, 2017;Fowler, 2012;Grabner, Zimmermann, Schicho, & Taschler, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid accumulation is a hallmark of NAFLD. Lowering lipid is accepted as an effective measure to ameliorate NAFLD [27][28][29]. Previous study showed that a proteoglycan named Fudan-Yueyang-Ganoderma lucidum (FYGL) extracted from Ganoderma lucidum had antihyperlipidemic effect, but the author paid most attention to the effect of FYGL on antidiabetic while no further study on liver protection [30].…”
Section: Discussionmentioning
confidence: 99%